International Law Aspects of Organizing and Regulating Tourism Activity Within the United Nations System - KALA, Nagima; ABAYDELDINOV, Yerbol (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
The present study illustrates the general characteristics of the United Nations system activity in the sphere of international tourism. Legal regulation of international tourism on a multilateral basis is carried out, first of all, within the United Nations system, which is tasked with adjusting international cooperation in solving the problems of economic, social, cultural and humanitarian character. The main international law documents on issues of international tourism regulations, which formed the basis for international tourism law, were elaborated and adopted within the framework of the United Nations system. After the World War II, International Union of Official Travel Organizations was engaged in processing and forming tourism terminology and definitions. After, in 1974 it was transformed into the United Nations World Tourism Organization. Thus, the main aim of the World Tourism Organization today is promoting tourism development, as well as elaborating general rules and provisions contributing to international tourism development and tourist exchange in the world community.